Performance of an Automated Versus a Manual Whole-Body Magnetic Resonance Imaging Workflow. Issue 8 (August 2018) - Stocker, Daniel; Finkenstaedt, Tim; Kuehn, Bernd; Nanz, Daniel; Klarhoefer, Markus; Guggenberger, Roman; Andreisek, Gustav; Kiefer, Berthold; Reiner, Caecilia S.
Abstract : Objectives: The aim of this study was to evaluate the performance of an automated workflow for whole-body magnetic resonance imaging (WB-MRI), which reduces user interaction compared with the manual WB-MRI workflow. Materials and Methods: This prospective study was approved by the local ethics committee. Twenty patients underwent WB-MRI for myopathy evaluation on a 3 T MRI scanner. Ten patients (7 women; age, 52 ± 13 years; body weight, 69.9 ± 13.3 kg; height, 173 ± 9.3 cm; body mass index, 23.2 ± 3.0) were examined with a prototypical automated WB-MRI workflow, which automatically segments the whole body, and 10 patients (6 women; age, 35.9 ± 12.4 years; body weight, 72 ± 21 kg; height, 169.2 ± 10.4 cm; body mass index, 24.9 ± 5.6) with a manual scan. Overall image quality (IQ; 5-point scale: 5, excellent; 1, poor) and coverage of the study volume were assessed by 2 readers for each sequence (coronal T2-weighted turbo inversion recovery magnitude [TIRM] and axial contrast-enhanced T1-weighted [ce-T1w] gradient dual-echo sequence). Interreader agreement was evaluated with intraclass correlation coefficients. Examination time, number of user interactions, and MR technicians' acceptance rating (1, highest; 10, lowest) was compared between both groups. Results: Total examination time was significantly shorter for automated WB-MRI workflow versus manual WB-MRI workflow (30.0 ± 4.2 vs 41.5 ± 3.4 minutes, P < 0.0001) with significantly shorter planning time (2.5 ± 0.8 vs 14.0 ± 7.0 minutes, P < 0.0001). Planning took 8% of the total examination time with automated versus 34% with manual WB-MRI workflow ( P < 0.0001). The number of user interactions with automated WB-MRI workflow was significantly lower compared with manual WB-MRI workflow (10.2 ± 4.4 vs 48.2 ± 17.2, P < 0.0001). Planning efforts were rated significantly lower by the MR technicians for the automated WB-MRI workflow than for the manual WB-MRI workflow (2.20 ± 0.92 vs 4.80 ± 2.39, respectively; P = 0.005). Overall IQ was similar between automated and manual WB-MRI workflow (TIRM: 4.00 ± 0.94 vs 3.45 ± 1.19, P = 0.264; ce-T1w: 4.20 ± 0.88 vs 4.55 ± .55, P = 0.423). Interreader agreement for overall IQ was excellent for TIRM and ce-T1w with an intraclass correlation coefficient of 0.95 (95% confidence interval, 0.86–0.98) and 0.88 (95% confidence interval, 0.70–0.95). Incomplete coverage of the thoracic compartment in the ce-T1w sequence occurred more often in the automated WB-MRI workflow ( P = 0.008) for reader 2. No other significant differences in the study volume coverage were found. Conclusions: In conclusion, the automated WB-MRI scanner workflow showed a significant reduction of the examination time and the user interaction compared with the manual WB-MRI workflow. Image quality and the coverage of the study volume were comparable in both groups.